LAND SUBSIDENCE DUE TO SEASONAL PUMPING OF GROUNDWATER IN SAGA PLAIN, JAPAN - Akira Sakai (Lowland Technology International, 2001)
In lowlands comprised of soft ground, land subsidence due to excessive groundwater pumping causes many problems, including damage to roads and structures, and an increased risk of flood due to the reduced drainage capacity of the system. Subsidence in Saga Plain, Japan, has been caused by fluctuating groundwater levels due to summer pumping for agriculture and winter recharge. The nature of land subsidence due to these groundwater level fluctuations is the focus of this paper. The characteristics of land subsidence and groundwater level were identified in both the Holocene clays and Pleistocene aquifer that form the hydrological system of the Saga Plain.